157k views
1 vote
Solve this problem out

Solve this problem out-example-1
User Shriram V
by
5.3k points

1 Answer

5 votes

Answer:

The equation D has (1-i) as a solution

Explanation:

we know that

The formula to solve a quadratic equation of the form


ax^(2) +bx+c=0

is equal to


x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}

Option A

in this problem we have


x^(2) +2x-2=0

so


a=1\\b=2\\c=-2

substitute in the formula


x=\frac{-2(+/-)\sqrt{2^(2)-4(1)(-2)}} {2(1)}


x=\frac{-2(+/-)√(12)} {2}


x=\frac{-2(+/-)2√(3)} {2}


x=-1(+/-)√(3)

Has two real solutions

Option B

in this problem we have


x^(2) +2x+2=0

so


a=1\\b=2\\c=2

substitute in the formula


x=\frac{-2(+/-)\sqrt{2^(2)-4(1)(2)}} {2(1)}


x=\frac{-2(+/-)√(-4)} {2}

Remember that


i=√(-1)


x=\frac{-2(+/-)2i} {2}


x=-1(+/-)i


x=-1+i


x=-1-i

Option C

in this problem we have


x^(2) -2x-2=0

so


a=1\\b=-2\\c=-2

substitute in the formula


x=\frac{-(-2)(+/-)\sqrt{-2^(2)-4(1)(-2)}} {2(1)}


x=\frac{2(+/-)√(12)} {2}


x=\frac{2(+/-)2√(3)} {2}


x=1(+/-)√(3)

Has two real solutions

Option D

in this problem we have


x^(2) -2x+2=0

so


a=1\\b=-2\\c=2

substitute in the formula


x=\frac{-(-2)(+/-)\sqrt{-2^(2)-4(1)(2)}} {2(1)}


x=\frac{2(+/-)√(-4)} {2}

Remember that


i=√(-1)


x=\frac{2(+/-)2i} {2}


x=1(+/-)i


x=1+i


x=1-i

therefore

The equation D has (1-i) as a solution

User Divinedragon
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.